2011
DOI: 10.1111/j.1600-0412.2011.01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality, fear of childbirth and cesarean delivery on demand

Abstract: The only psychological variable associated with the choice for cesarean section on maternal request was the fear of childbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 26 publications
2
41
0
1
Order By: Relevance
“…This finding urges that special attention to be given to decrease the childbirth anxiety due to its impact on abnormal pregnancy outcomes mainly of cesarean sections. Previous studies supports this suggestion as their studies also revealed that request for caesarean sections were higher among pregnant women particularly nulliparous with more childbirth fears (Fenwick et al, 2009;Hall et al, 2012;Handelzalts et al, 2012;Laursen et al, 2009;Nieminen et al, 2009;Rubertsson et al, 2014). Evidences also established the relationship between high levels of pregnancy anxiety and adverse labour outcomes such as preterm births, low birth weight and mode of delivery (Catov et al, 2010;Hernandez-Martinez et al, 2011;Loomans et al, 2013;Rauchfuss & Maier, 2011).…”
Section: Childbirth Anxietymentioning
confidence: 59%
See 1 more Smart Citation
“…This finding urges that special attention to be given to decrease the childbirth anxiety due to its impact on abnormal pregnancy outcomes mainly of cesarean sections. Previous studies supports this suggestion as their studies also revealed that request for caesarean sections were higher among pregnant women particularly nulliparous with more childbirth fears (Fenwick et al, 2009;Hall et al, 2012;Handelzalts et al, 2012;Laursen et al, 2009;Nieminen et al, 2009;Rubertsson et al, 2014). Evidences also established the relationship between high levels of pregnancy anxiety and adverse labour outcomes such as preterm births, low birth weight and mode of delivery (Catov et al, 2010;Hernandez-Martinez et al, 2011;Loomans et al, 2013;Rauchfuss & Maier, 2011).…”
Section: Childbirth Anxietymentioning
confidence: 59%
“…The study concluded that fear of childbirth was the only psychological variable associated with the choice for caesarean section. (Handelzalts et al, 2012). Nieminen et al (2009) reported that maternal request for caesarean section was out of fear of intense childbirth.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Cultural factors, the structure of antenatal care and delivery services, as well as how they are funded, are likely to influence preferences for CS [14]. However, it may be argued that the perception of the upcoming birth is deeply embedded in a woman's personality and prior experiences, including traumas [15][16][17][18]. Based on this assumption, reported preference for CS would not be related to external factors and thus may not vary across countries.…”
Section: Introductionmentioning
confidence: 99%
“…FOC is often the reason for caesarean section on the woman's request [1,[15][16][17], which probably means that elective caesarean section is more common among these women [9,11,16]. This might reflect that these women doubt their own capacity to cope with the upcoming labour and birth.…”
Section: Introductionmentioning
confidence: 99%